Secondary battery and electric device

CN119301789APending Publication Date: 2025-01-10CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380044858.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing electrode materials with high theoretical capacity are difficult to effectively exert their capacity in secondary batteries and have poor cycle performance, mainly due to the large volume expansion rate of silicon-based materials during the charge and discharge process and the consumption of active lithium by surface groups.

Method used

A silicon-carbon composite material with a three-dimensional network cross-linked pore structure is used as the negative electrode material, and specific compounds are added to the electrolyte, such as trimethyl phosphate or tris (trimethylsilane) borate, through interaction with the silicon-carbon composite material. The combination of active groups stabilizes the active groups, reduces volume expansion and active lithium consumption, and improves the first Coulombic efficiency and cycle capacity retention rate of the battery.

Benefits of technology

The first Coulombic efficiency and cycle capacity retention rate of secondary batteries are significantly improved, the cycle life of the battery is extended, and the energy density and structural stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301789A_ABST
    Figure CN119301789A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery. The secondary battery comprises a negative pole piece and an electrolyte, wherein the negative pole piece comprises a silicon-carbon composite material with a three-dimensional network cross-linked pore structure; the electrolyte comprises a first component, and the first component comprises at least one of compounds shown in a formula I and a formula II. Through cooperation of the three-dimensional network cross-linked pore structure of the silicon-carbon composite material and the first component in the electrolyte, the volume effect of the active material in the charging and discharging process is inhibited, and the first coulombic efficiency and cycle stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Secondary batteries and electrical devices Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] As market demands for battery energy continue to rise, the use of high-capacity electrode materials has become a consensus in the field. However, many electrode materials with high theoretical capacities struggle to fully realize their full capacity. Improving battery capacity through the coordination of various battery components is a pressing technical challenge in this field.

[0004] Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery. By matching the electrolyte and the negative electrode material, the initial coulombic efficiency and cycle capacity retention rate of the battery are improved, thereby optimizing the battery's capacity utilization and cycle performance.

[0006] A first aspect of the present application provides a secondary battery, characterized in that it includes a negative electrode plate and an electrolyte; the negative electrode plate includes a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; the electrolyte includes a first component, and the first component includes at least one of the compounds represented by Formula I and Formula II,

[0007] in, It means that M and O can be connected by a single bond or a double bond. When M and O are double-bonded, there is no chemical bond between O and R4 or R3. It means that M1 and O can be connected by a single bond or a double bond. When M1 and O are double-bonded, there is no chemical bond between O and R7. R1, R2, R3, R4, R5, R6, and R7 are each independently selected from fluorine, fluorine-substituted or unsubstituted C1 to C 10 A hydrocarbon group, an aryl group, a carbonyl group, a carboxyl group, an ester group, a cyano group, a silane group or an ether group, wherein M and M1 each independently contain P, S, Si or B.

[0008] The silicon-carbon composite material with a three-dimensional network cross-linked pore structure has a stable porous skeleton and good mechanical strength. It can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content, thereby improving the cycle performance of the battery. At the same time, the M element of the first component in the electrolyte can combine with the active groups on the silicon-carbon composite material, such as hydroxyl, carboxyl, and amino groups, to stabilize the active groups, reduce their consumption of active lithium, improve the first coulomb effect of the battery, and improve the capacity of the battery. The stabilization of the active groups on the silicon-carbon composite material can also further reduce the capacity decay of the battery during the cycle and improve the cycle performance of the battery. Furthermore, the first component additive can generate inorganic substances containing the M element in the solid electrolyte membrane (SEI) on the surface of the silicon-carbon composite material, such as phosphates, sulfates, etc., which can further improve the strength of the SEI membrane, reduce its rupture caused by the expansion of the silicon negative electrode, and improve the cycle performance of the battery.

[0009] In any embodiment, the specific surface area of ​​the silicon-carbon composite material is SSA m 2 / g,

[0010] Based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g,

[0011] EL: SSA is 0.0001~0.03, and can be optionally 0.0004~0.01.

[0012] The larger the specific surface area of ​​the silicon-carbon composite material, the higher its surface functional group content. When the ratio EL:SSA between the mass proportion of the first component in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the first component can effectively "passivate" the active groups on the silicon-carbon composite material, improving the battery's capacity and cycle performance.

[0013] In any embodiment,

[0014] Based on the total mass of the electrolyte, the mass percentage of the first component is EL g / g, and in the peripheral region of the silicon-carbon composite material, the mass percentage of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material is B1, wherein the peripheral region of the silicon-carbon composite material is a region extending from the outer surface of the silicon-carbon composite material to the interior of the silicon-carbon composite material within a distance of r / 2, where r represents the short diameter of the silicon-carbon composite material.

[0015] EL: B1 is 0.001~0.1, and can be optionally 0.005~0.06.

[0016] Compared to the silicon within the silicon-carbon composite, the silicon in the outer region of the composite is more likely to retain active groups during the preparation process and is less likely to be constrained by the carbon skeleton, resulting in more significant volume expansion. When the ratio of the mass fraction of the first component in the electrolyte to the mass percentage (B1) of the silicon in the composite relative to the total mass of the composite falls within the above range, the first component can "passivate" the active groups on the silicon, further improving the battery's initial coulombic efficiency and cycle capacity retention.

[0017] In any embodiment, the total pore volume of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1 g / cm 3 Based on the total mass of the electrolyte, the mass ratio of the first component is EL g / g, and EL:V1 is 1 to 30, and preferably 2 to 15.

[0018] When the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material meets the above range, the first component can easily enter the pore structure of the silicon-carbon composite material, forming mutual cooperation with it to further improve the capacity utilization level and cycle capacity retention rate of the battery.

[0019] In any embodiment, in the peripheral area of ​​the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5.

[0020] In the peripheral region of the silicon-carbon composite material, when the mass percentage A1 of the carbon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material meet the above ranges, the mass of silicon in the pore structure of the silicon-carbon composite material is relatively high, which can significantly increase the capacity of the negative electrode active material, and the voltage for metal ion embedding is low, which is conducive to the embedding of metal ions, thereby improving the cycle performance of the secondary battery. At the same time, the three-dimensional network cross-linked pore structure can inhibit the volume expansion of silicon during the cycle, improve the structural stability of the negative electrode active material, and thus improve the cycle performance of the battery.

[0021] In any embodiment, the mass percentage A of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has a decreasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, and the mass percentage B of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has an increasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material.

[0022] Since the silicon-carbon composite material may be an irregular shape, the geometric center of the silicon-carbon composite material can be equated with the geometric center of a rectangular parallelepiped tangent to it. From the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, the mass percentage of carbon (A) gradually decreases, while the mass percentage of silicon (B) gradually increases. The silicon content in the pore structure of the silicon-carbon composite material gradually increases. A relatively high silicon content can significantly increase the capacity of the negative electrode active material. Furthermore, the increasing silicon content from the outer surface to the center causes the number of active functional groups on the surface of the silicon-based particles to decrease, making the carbon-based particles' inhibitory effect on silicon expansion increasingly significant, thereby further improving the battery's capacity utilization and cycle performance.

[0023] In any embodiment, the specific surface area SSA of the silicon-carbon composite material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 3m 2 / g≤SSA≤7m 2 / g.

[0024] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of ​​the silicon-carbon composite material is large, the kinetic properties of the material are good, and it is beneficial to improve the first coulombic efficiency of the battery.

[0025] In any embodiment, the silicon-carbon composite material includes carbon matrix particles and silicon nanoparticles, the carbon matrix particles include a three-dimensional network cross-linked pore structure; at least a portion of the silicon nanoparticles is disposed in the three-dimensional network cross-linked pore structure.

[0026] The carbon matrix particles of the present application have a stable porous skeleton structure, a strong supporting capacity, a high stress capacity, and excellent mechanical properties and electrical conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for embedding silicon-based nanoparticles, can be used for large-scale silicon storage, and effectively increase the silicon loading capacity in the silicon-carbon composite material. After the carbon matrix particles and the silicon-based nanoparticles are compounded, the electrical conductivity of the silicon-carbon composite material can be improved, while the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of the silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material and improving the cycle stability and lithium storage capacity of the silicon-carbon composite material. Therefore, when the silicon-carbon composite material is applied to a secondary battery, the cycle performance and energy density of the secondary battery can be improved.

[0027] In any embodiment, the silicon nanoparticles include one or more of silicon oxide compounds, pre-lithium silicon oxide compounds, amorphous silicon, crystalline silicon, and silicon-carbon composites, and may be amorphous silicon.

[0028] In any embodiment, the carbon matrix includes one or more of graphite, soft carbon, and hard carbon.

[0029] In any embodiment, the mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.

[0030] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.

[0031] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3 The compaction density of the silicon-carbon composite material after 20 powder compaction tests under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.

[0032] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.

[0033] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.

[0034] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.

[0035] The compound represented by formula I is selected from one or more of the following compounds:

[0036] Trimethyl phosphate Triphenyl phosphate Tris(trimethylsilyl)phosphine Tributyl phosphate Diethyl sulfate Bis(trimethylsilyl) sulfate Ethyl silicate Tetrapropoxysilane Tetraphenyl silicate Tetraallyl silicate Tetraethyl orthosilicate

[0037] The compound represented by formula II is selected from one or more of the following compounds:

[0038] Diisopropyl sulfite tris(trimethylsilyl)borate triethyl borate triphenylborate Triisopropyl borate

[0039] The compound represented by Formula I and the compound represented by Formula II above include elements B, P, S, or Si. Elements B and Si provide empty orbitals that can bind to oxygen elements in the surface active groups of the silicon-carbon composite material, thereby "passivating" the active groups and improving the initial coulombic efficiency and cycle performance of the battery. Elements P and S provide electrons that can bind to hydrogen elements in the surface active groups of the silicon-carbon composite material, thereby "passivating" the active groups and improving the initial coulombic efficiency and cycle performance of the battery.

[0040] In any embodiment, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.

[0041] A second aspect of the present application provides an electrical device comprising the secondary battery of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0043] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0044] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0045] Description of reference numerals: 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate. DETAILED DESCRIPTION

[0046] Below, the embodiments of the binder, preparation method, electrode, battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0047] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0050] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0051] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0052] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0053] With the expansion of the application scope of secondary batteries, the requirements for secondary battery performance, such as energy density, are gradually increasing. Silicon-based materials have high specific capacity and are suitable for negative electrode materials of high energy density batteries. However, the volume expansion rate of silicon-based materials is large during the charge and discharge process, resulting in poor battery cycle performance. Moreover, compared with traditional carbon-based materials, silicon-based materials are more likely to introduce more surface groups during the production and preparation process. For example, silicon-based materials are more likely to introduce carboxyl groups or hydroxyl groups on their surface when treated with acid, and silicon-based materials are more likely to introduce amino groups on their surface when treated with alkali. The presence of surface groups easily consumes active lithium, affecting the capacity of the battery.

[0054] Based on this, the present application provides a secondary battery comprising: a negative electrode plate and an electrolyte, wherein the negative electrode plate comprises a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; the electrolyte comprises a first component, wherein the first component comprises at least one of the compounds represented by Formula I and Formula II,

[0055] in, It means that M and O can be connected by a single bond or a double bond. When M and O are double-bonded, there is no chemical bond between O and R4 or R3. It means that M1 and O can be connected by a single bond or a double bond. When M1 and O are double-bonded, there is no chemical bond between O and R7. R1, R2, R3, R4, R5, R6, and R7 are each independently selected from fluorine, fluorine-substituted or unsubstituted C1 to C 10 A hydrocarbon group, an aryl group, a carbonyl group, a carboxyl group, an ester group, a cyano group, a silane group or an ether group, wherein M and M1 each independently contain P, S, Si or B.

[0056] In this article, the terms "C1~C 10 "Hydrocarbon" refers to a hydrocarbon group having 1 to 10 carbon atoms. 10 Non-limiting examples of hydrocarbon groups may include methyl (CH3-), ethyl (C2H5-), isopropyl ((CH3)2CH-), vinyl (CH2=CH-), propynyl (HC≡CCH2-), methylene (-CH2-).

[0057] As used herein, "aryl" refers to a group formed by losing a hydrogen atom from an aromatic hydrocarbon molecule. Non-limiting examples of aryl include phenyl, naphthyl, and the like.

[0058] As used herein, "carbonyl" refers to

[0059] In this context, "carboxyl" refers to

[0060] In this context, "ester group" refers to Wherein, R is a C1-C3 hydrocarbon group.

[0061] As used herein, "cyano" refers to -C≡N.

[0062] As used herein, the term "silyl" refers to a -Si(R1)(R2)(R3) group, wherein R1, R2, and R3 are each independently selected from hydrogen, a substituted or unsubstituted C1-C3 alkyl group. By way of example, silyl groups include, but are not limited to, -SiH3 and -Si(CH3)3.

[0063] As used herein, "ether group" refers to -RO-R'-, wherein R and R' are C1-C3 hydrocarbon groups.

[0064] In this article, the three-dimensional network cross-linked pore structure generally refers to a structure in which two or more pores are interconnected or intertwined and share pore volume in a silicon-carbon composite material, especially in a pore structure formed by carbon matrix particles.

[0065] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.

[0066] The silicon-carbon composite material with a three-dimensional network cross-linked pore structure has a stable porous skeleton and good mechanical strength. It can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content, thereby improving the cycle performance of the battery. At the same time, the M element of the first component in the electrolyte can combine with the active groups on the silicon-carbon composite material, such as hydroxyl, carboxyl, and amino groups, to stabilize the active groups, reduce their consumption of active lithium, improve the first coulomb effect of the battery, and improve the capacity of the battery. The stabilization of the active groups on the silicon-carbon composite material can also further reduce the capacity decay of the battery during the cycle and improve the cycle performance of the battery. Furthermore, the first component additive can generate inorganic substances containing the M element in the solid electrolyte membrane (SEI) on the surface of the silicon-carbon composite material, such as phosphates, sulfates, etc., which can further improve the strength of the SEI membrane, reduce its rupture caused by the expansion of the silicon negative electrode, and improve the cycle performance of the battery.

[0067] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is SSA m 2 / g, based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, and EL:SSA is 0.0001-0.03, and can be optionally 0.0004-0.01.

[0068] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is SSA m 2 / g, the mass proportion of the first component in the electrolyte is EL g / g, and EL:SSA can be selected from 0.0001, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02 or 0.03 g / m 2 .

[0069] In this article, specific surface area SSA is a well-known meaning in the art, usually the surface area is expressed in m 2 The unit of % is expressed in g and can be measured using methods and instruments known in the art. For example, it can be measured using an inert gas (e.g., nitrogen) adsorption specific surface area analysis method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, USA.

[0070] The larger the specific surface area of ​​the silicon-carbon composite material, the higher its surface functional group content. When the ratio EL:SSA between the mass proportion of the first component in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the first component can effectively "passivate" the active groups on the silicon-carbon composite material, improving the battery's capacity and cycle performance.

[0071] In some embodiments, the mass percentage of the first component in the electrolyte is EL g / g. In the peripheral region of the silicon-carbon composite material, the mass percentage of silicon in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material is B1, wherein the peripheral region of the silicon-carbon composite material is the region extending from the outer surface of the silicon-carbon composite material to the interior of the silicon-carbon composite material within a distance r / 2, where r represents the minor diameter of the silicon-carbon composite material, and EL:B1 is 0.001 to 0.1, and can optionally be 0.005 to 0.06.

[0072] The three-axis diameter characterization method can be used to characterize the particle size of the silicon-carbon composite material. The specific characterization method is as follows: the long diameter l and the short diameter r are measured on the plane projection of the silicon-carbon composite material, and the thickness h of the silicon-carbon composite material is measured in the direction perpendicular to the projection plane; it can also be understood as placing the silicon-carbon composite material in a rectangular parallelepiped tangent to it, with the long side of the rectangular parallelepiped being l, the short side being r, and the thickness being h, to reflect the actual size of the silicon-carbon composite material.

[0073] The silicon content can be determined by inductively coupled plasma (ICP) emission spectroscopy test, as follows: a silicon-carbon composite material is taken as a sample, the sample is digested with aqua regia and hydrofluoric acid HF, and the solution digested for 15 minutes and the completely digested solution are taken for ICP testing. The silicon content in the solution digested for 45 minutes is the silicon content in the "peripheral area of ​​the silicon-carbon composite material."

[0074] In some embodiments, the ratio EL:B1 between the mass percentage of the first component in the electrolyte and the mass percentage B1 of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material can be selected to be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1.

[0075] Compared to the silicon within the silicon-carbon composite, the silicon in the outer region of the composite is more likely to retain active groups during the preparation process and is less likely to be constrained by the carbon skeleton, resulting in more significant volume expansion. When the ratio of the mass fraction of the first component in the electrolyte to the mass percentage (B1) of the silicon in the composite relative to the total mass of the composite falls within the above range, the first component can "passivate" the active groups on the silicon, further improving the battery's initial coulombic efficiency and cycle capacity retention.

[0076] In some embodiments, the total pore volume of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1 cm 3 / g, the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is 1 to 30, and can be optionally 2 to 15.

[0077] The pore volume test method for different pore sizes can refer to GB / T 19587-2004, using the mesopore pore size distribution test BJH (Barret Joyner Halenda), using the gas adsorption and desorption method under the micro-mesopore model and selecting the adsorption branch data to measure and calculate the total pore volume V1 of pores with a pore size greater than 100 nm.

[0078] In some embodiments, the total pore volume of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1 cm 3 / g, the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material can be preferably 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.

[0079] When the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material meets the above range, the first component can easily enter the pore structure of the silicon-carbon composite material, forming mutual cooperation with it to further improve the capacity utilization level and cycle capacity retention rate of the battery.

[0080] In some embodiments, in the peripheral region of the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5.

[0081] The carbon content can be analyzed by infrared absorption carbon-sulfur content analysis according to the GB / T20123-2006 test standard, specifically as follows: take the silicon-carbon composite material as a sample, and the carbon content at 20 minutes of testing is the carbon content of the "peripheral area of ​​the silicon-carbon composite material".

[0082] In the peripheral region of the silicon-carbon composite material, when the mass percentage A1 of the carbon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material meet the above ranges, the mass of silicon in the pore structure of the silicon-carbon composite material is relatively high, which can significantly increase the capacity of the negative electrode active material, and the voltage for metal ion embedding is low, which is conducive to the embedding of metal ions, thereby improving the cycle performance of the secondary battery. At the same time, the three-dimensional network cross-linked pore structure can inhibit the volume expansion of silicon during the cycle, improve the structural stability of the negative electrode active material, and further improve the cycle performance of the battery.

[0083] In some embodiments, the mass percentage A of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has a decreasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, and the mass percentage B of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has an increasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material.

[0084] Since the silicon-carbon composite material may be an irregular shape, the geometric center of the silicon-carbon composite material can be equated with the geometric center of a rectangular parallelepiped tangent to it. From the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, the mass percentage of carbon (A) gradually decreases, while the mass percentage of silicon (B) gradually increases. The silicon content in the pore structure of the silicon-carbon composite material gradually increases. A relatively high silicon content can significantly increase the capacity of the negative electrode active material. Furthermore, the increasing silicon content from the outer surface to the center causes the number of active functional groups on the surface of the silicon-based particles to decrease, making the carbon-based particles' inhibitory effect on silicon expansion increasingly significant, thereby further improving the battery's capacity utilization and cycle performance.

[0085] In some embodiments, the specific surface area SSA of the silicon-carbon composite material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 3m 2 / g≤SSA≤7m 2 / g.

[0086] In some embodiments, the specific surface area SSA of the silicon-carbon composite material can be selected to be 2 m 2 / g、3m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g or 10m 2 / g, or a range consisting of any two of the above values.

[0087] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of ​​the silicon-carbon composite material is large, the kinetic properties of the material are good, and it is beneficial to improve the first coulombic efficiency of the battery.

[0088] In some embodiments, the silicon-carbon composite material includes: carbon matrix particles and silicon nanoparticles, the carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon nanoparticles is disposed in the three-dimensional network cross-linked pore structure.

[0089] The carbon matrix particles of the present application have a stable porous skeleton structure, a strong supporting capacity, a high stress capacity, and excellent mechanical properties and electrical conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for embedding silicon-based nanoparticles, can be used for large-scale silicon storage, and effectively increase the silicon loading capacity in the silicon-carbon composite material. After the carbon matrix particles and the silicon-based nanoparticles are compounded, the electrical conductivity of the silicon-carbon composite material can be improved, while the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of the silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material and improving the cycle stability and lithium storage capacity of the silicon-carbon composite material. Therefore, when the silicon-carbon composite material is applied to a secondary battery, the cycle performance and energy density of the secondary battery can be improved.

[0090] In some embodiments, the silicon nanoparticles include one or more of silicon oxides, amorphous silicon, crystalline silicon, and silicon-carbon composites, and may be amorphous silicon.

[0091] In some embodiments, the carbon matrix includes one or more of graphite, soft carbon, and hard carbon.

[0092] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.

[0093] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material may be 40%, 45%, 50%, 55% or 60%.

[0094] The quality of silicon nanoparticles in silicon-carbon composite materials can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, in which the solid to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for quantitative analysis of trace elements.

[0095] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.

[0096] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20,000 N is P21g / cm3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.

[0097] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.

[0098] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.

[0099] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.

[0100] In some embodiments, the compound represented by Formula I is selected from one or more of the following compounds:

[0101] Trimethyl phosphate Triphenyl phosphate Tris(trimethylsilyl)phosphine Tributyl phosphate Diethyl sulfate Bis(trimethylsilyl) sulfate Ethyl silicate Tetrapropoxysilane Tetraphenyl silicate Tetraallyl silicate Tetraethyl orthosilicate

[0102] The compound represented by formula II is selected from one or more of the following compounds:

[0103] Diisopropyl sulfite tris(trimethylsilyl)borate triethyl borate triphenylborate Triisopropyl borate

[0104] The compound represented by Formula I and the compound represented by Formula II above include elements B, P, S, or Si. Elements B and Si provide empty orbitals that can bind to oxygen elements in the surface active groups of the silicon-carbon composite material, thereby "passivating" the active groups and improving the initial coulombic efficiency and cycle performance of the battery. Elements P and S provide electrons that can bind to hydrogen elements in the surface active groups of the silicon-carbon composite material, thereby "passivating" the active groups and improving the initial coulombic efficiency and cycle performance of the battery.

[0105] In some embodiments, a secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0106] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0107] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0108] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0109] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0110] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0111] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0112] In some embodiments, a secondary battery includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode film layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0113] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0114] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0115] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0116] In some embodiments, the positive electrode active material is a nickel-rich material, and the molar ratio of nickel in the transition metal of the positive electrode active material is higher than 85%.

[0117] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0118] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0119] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0120] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0121] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0122] In some embodiments, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.

[0123] In one embodiment of the present application, an electric device is provided, comprising the secondary battery of any embodiment.

[0124] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 1 with a square structure as an example.

[0125] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.

[0126] An electrical device includes the secondary battery provided in this application. The secondary battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0127] Figure 3 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0128] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0129] Example

[0130] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0131] Primary and secondary batteries

[0132] Example 1

[0133] (1) Preparation of silicon-carbon composite materials

[0134] A gas containing a silicon precursor is supplied to carbon matrix particles having a three-dimensional network cross-linked pore structure; silicon nanoparticles attached to the carbon matrix particles are generated from the silicon precursor by chemical vapor deposition to obtain a silicon-carbon composite material. The silicon precursor is silane, and the carbon matrix is ​​hard carbon.

[0135] (2) Preparation of negative electrode sheet

[0136] The negative electrode active material (silicon-carbon composite material), conductive carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) are fully stirred and mixed in an appropriate amount of deionized water at a weight ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying and other processes, a negative electrode sheet is obtained.

[0137] (3) Preparation of positive electrode sheet

[0138] Aluminum foil with a thickness of 8 μm was used as the positive electrode current collector. 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ), the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) in a weight ratio of 93:2:5, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0139] (4) Preparation of electrolyte

[0140] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent, and 1wt% tris(trimethylsilyl)borate is added as an additive to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0141] (5) Isolation membrane

[0142] Polypropylene film is used as the isolation film.

[0143] (6) Preparation of batteries

[0144] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrode sheets to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell and placed in an aluminum shell. The cells are then baked at 80°C to remove moisture. The electrolyte is then injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the lithium-ion battery product of Example 1.

[0145] Examples 2-5

[0146] The preparation methods of the batteries of Examples 2-5 are similar to that of Example 2, but the type of the first component is adjusted. The specific parameters are shown in Table 1.

[0147] Examples 6-9

[0148] The preparation methods of the batteries of Examples 6-9 are similar to that of Example 2, but the content of the first component is adjusted. The specific parameters are shown in Table 1.

[0149] Examples 10-13

[0150] The preparation methods of the batteries of Examples 10-13 are similar to those of Example 2, but the deposition positions of the silicon-based particles in the silicon-carbon composite material are adjusted to adjust the ratio of EL:B1. The specific parameters are shown in Table 1.

[0151] Examples 14-17

[0152] The preparation methods of the batteries of Examples 14-17 are similar to that of Example 2, but the ratio of large and small pores in the silicon-carbon composite material is adjusted to adjust the ratio of EL:V1.

[0153] Comparative Example 1

[0154] The preparation method of the battery of Comparative Example 1 is similar to that of Example 1, but the first component is not added to the electrolyte.

[0155] Comparative Example 2

[0156] The preparation method of the battery of Comparative Example 2 is similar to that of Example 1, but the pore structure of the carbon matrix particles of Comparative Example 2 is a honeycomb pore structure.

[0157] Comparative Example 3

[0158] The preparation method of the battery of Comparative Example 3 is similar to that of Example 2, but the pore structure of the carbon matrix particles of Comparative Example 3 is a honeycomb pore structure.

[0159] Comparative Example 4

[0160] The preparation method of the battery of Comparative Example 4 is similar to that of Example 3, but the pore structure of the carbon matrix particles of Comparative Example 4 is a honeycomb pore structure.

[0161] Comparative Example 5

[0162] The preparation method of the battery of Comparative Example 5 is similar to that of Example 4, but the pore structure of the carbon matrix particles of Comparative Example 5 is a honeycomb pore structure.

[0163] Comparative Example 6

[0164] The preparation method of the battery of Comparative Example 6 is similar to that of Example 5, but the pore structure of the carbon matrix particles of Comparative Example 6 is a honeycomb pore structure.

[0165] 2. Test Method

[0166] 1. Silicon-carbon composite materials

[0167] 1) Structural characterization of silicon-carbon composites

[0168] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.

[0169] 2) Specific surface area SSA of silicon-carbon composite material

[0170] The specific surface area was tested using the gas adsorption method according to the GB / T19587-2017 test standard, as follows: the battery was disassembled, the negative electrode was scraped and the binder was removed by high-temperature ablation. The powder material was then taken as a silicon-carbon composite material sample. The sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of ​​the negative electrode active material.

[0171] The BET calculation formula is as follows:

[0172] Where n a —amount of adsorbed gas, in mol / g; p / p0 —relative pressure; nm —monolayer adsorption capacity; C represents a correction parameter, which is used to limit the number of adsorption layers on the adsorbent surface.

[0173] 3) Pore diameter of silicon-carbon composite material

[0174] The pore size is tested by gas adsorption method according to the test standards GB / T19587-2017 & GB / T21650.2-2008. The specific test method is as follows: a silicon-carbon composite material is taken as a sample, and the sample tube is immersed in liquid nitrogen at -196°C. Nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on the relationship between the volume of each pore size and the corresponding partial pressure.

[0175] 4) Powder compaction density

[0176] Refer to GB / T 24533-2009 and use an electronic pressure testing machine (such as UTM7305) to test: place a powder sample of a certain mass G on a special compaction mold (bottom area S), set different pressures (20000N or 50000N can be used in this application), maintain the pressure for 20s, release the pressure, wait for 10s, and read the thickness H of the powder after compaction under the pressure on the equipment. The compaction density under the pressure can be calculated, and the compaction density of the material under the pressure = G / (H*S).

[0177] 5) Characterization of silicon and carbon element distribution in silicon-carbon composites

[0178] The elemental distribution of the particle cross section was tested by energy dispersive ion polishing cross section element analysis according to the GB-T17359-2012 test standard.

[0179] 6) Test of silicon content in silicon-carbon composite materials

[0180] The silicon content was determined by emission spectroscopy (Inductively coupled plasma, ICP), specifically as follows: a silicon-carbon composite material was taken as a sample, and the sample was digested with aqua regia and hydrofluoric acid HF. The solution digested for 15 minutes and the solution completely digested were taken for ICP testing. The silicon content in the solution digested for 45 minutes was the silicon content in the "peripheral area of ​​the silicon-carbon composite material", and the difference between the silicon content in the solution completely digested and that in the solution digested for 1 hour was the silicon content in the "central area of ​​the silicon-carbon composite material".

[0181] 7) Carbon content test in silicon-carbon composite materials 15

[0182] The carbon-sulfur content analysis by infrared absorption method is tested according to the GB / T20123-2006 test standard, as follows: the silicon-carbon composite material is taken as a sample, and the carbon content at 20 minutes of testing is the carbon content of the "peripheral area of ​​the silicon-carbon composite material", and the difference between the carbon content at 20 minutes of testing and the end of the test is the carbon content of the "peripheral area of ​​the silicon-carbon composite material".

[0183] 8) Short diameter r test of silicon-carbon composite materials

[0184] The short diameter r is measured according to the three-axis characterization method, specifically as follows: the short diameter r is measured on a plane projection diagram of the silicon-carbon composite material.

[0185] 2. Battery performance

[0186] 1) First Coulombic efficiency

[0187] At 25°C, the secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.33C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage to a current of ≤0.05C, allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V. The coulombic efficiency of the battery in the first cycle was calculated by dividing the first charge capacity of the battery by the discharge capacity.

[0188] 2) Cycle capacity retention rate

[0189] At 25°C, the secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method, and the capacity retention of the lithium-ion batteries after 800 cycles was calculated.

[0190] 3. Analysis of test results of various embodiments and comparative examples

[0191] Secondary batteries of various embodiments and comparative examples were prepared according to the above methods, and various parameters were measured. The results are shown in Table 1 below.

[0192] Table 1

[0193] According to the results in Table 1, the negative electrode active material of the batteries of Examples 1-17 is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure, and the electrolyte contains the compound represented by Formula I or Formula II. Compared with the battery in Comparative Example 1 in which the negative electrode active material is a silicon-carbon composite material with a honeycomb pore structure and the electrolyte does not contain the compound represented by Formula I or Formula II, and the batteries in Comparative Examples 2-6 in which the negative electrode active material is a silicon-carbon composite material with a honeycomb pore structure and the electrolyte contains the compound represented by Formula I or Formula II, the batteries of Examples 1-17 exhibit higher first coulombic efficiency and higher cycle capacity retention.

[0194] In the comparative example, the negative electrode is a silicon-carbon composite material with a honeycomb pore structure. Silicon particles are not easily deposited inside the honeycomb pore structure. Therefore, the mass content of silicon-based particles in the silicon-carbon composite material with a honeycomb pore structure is low, only 7%, and the silicon element is concentrated on the surface distribution of the composite material. The carbon matrix can hardly play a role in limiting the expansion of silicon-based particles, and the battery's cycle performance is poor.

[0195] From the comparison between Examples 7 and 8 and Examples 6 and 9, it can be seen that controlling the ratio EL:SSA between the mass proportion EL of the first component in the electrolyte and the specific surface area of ​​the silicon-carbon composite material in the range of 0.0004 to 0.01 is beneficial to further improve the first coulombic efficiency and cycle capacity retention rate of the battery.

[0196] It can be seen from Examples 10-13 that by further controlling EL:B1 within the range of 0.005 to 0.06, the first coulombic efficiency and cycle capacity retention rate of the battery will be further improved.

[0197] From Examples 14-17, it can be seen that further making EL:V1 between 1 and 30 cm 3 / g range, the battery's first coulombic efficiency and cycle capacity retention rate will be further improved.

[0198] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: include A negative electrode plate, the negative electrode plate comprising a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; and An electrolyte, wherein the electrolyte comprises a first component, wherein the first component comprises at least one of the compounds represented by formula I and formula II, in, It means that M and O can be connected by a single bond or a double bond. When M and O are connected by a double bond, there is no chemical bond between O and R4 or R3; It means that M1 and O can be connected by a single bond or a double bond. When M1 and O are connected by a double bond, there is no chemical bond between O and R7; R1, R2, R3, R4, R5, R6, and R7 each independently contain fluorine, fluorine-substituted or unsubstituted C1~C 10 A hydrocarbon group, an aryl group, a carbonyl group, a carboxyl group, an ester group, a cyano group, a silane group or an ether group, M and M1 each independently contain P, S, Si or B.

2. The secondary battery according to claim 1, characterized in that: The specific surface area of ​​the silicon-carbon composite material is SSA m 2 / g, Based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, EL: SSA is 0.001~0.02, and can be optionally 0.004~0.

01.

3. The secondary battery according to claim 1 or 2, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, In the peripheral area of ​​the silicon-carbon composite material, the mass percentage of silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material is B1, wherein The peripheral region of the silicon-carbon composite material is a region extending from the outer surface of the silicon-carbon composite material to the inside of the silicon-carbon composite material within a distance of r / 2, where r represents the short diameter of the silicon-carbon composite material. EL: B1 is 0.001~0.1, and can be optionally 0.005~0.

06.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The total pore volume of the pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1cm 3 / g, based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, EL: V1 is 1-30, and preferably 2-15.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The compound represented by formula I is selected from one or more of the following compounds: Trimethyl phosphate, triphenyl phosphate, tri(trimethylsilyl)phosphide, tributyl phosphate, diethyl sulfate, bis(trimethylsilyl) sulfate, ethyl silicate, tetrapropoxysilane, tetraphenyl silicate, tetraallyl silicate, tetraethyl orthosilicate; The compound represented by formula II is selected from one or more of the following compounds: Diisopropyl sulfite, tris(trimethylsilyl)borate, triethyl borate, triphenylborate, triisopropyl borate.

6. The secondary battery according to any one of claims 3 to 5, characterized in that: In the peripheral area of ​​the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.

5.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The mass percentage A of the carbon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has a decreasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, and the mass percentage B of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has an increasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The specific surface area SSA of the silicon-carbon composite material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 3m 2 / g≤SSA≤7m 2 / g.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The silicon-carbon composite material comprises: carbon matrix particles, the carbon matrix particles comprising a three-dimensional network cross-linked pore structure; and silicon nanoparticles, at least a portion of which is disposed in the three-dimensional network cross-linked pore structure.

10. The secondary battery according to claim 9, characterized in that: The silicon nanoparticles include one or more of silicon oxides, amorphous silicon, crystalline silicon and silicon-carbon composites, and may be amorphous silicon.

11. The secondary battery according to claim 9 or 10, characterized in that: The carbon matrix includes one or more of graphite, soft carbon and hard carbon.

12. The secondary battery according to any one of claims 9 to 11, characterized in that: The mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.

13. The secondary battery according to any one of claims 1 to 12, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.

10.

14. The secondary battery according to any one of claims 1 to 13, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.

35.

15. The secondary battery according to any one of claims 1 to 14, characterized in that: The secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.

16. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 15.

Citation Information

Cited By

  • Anti-overcharge additive, non-aqueous electrolyte containing same and non-aqueous electrolyte battery

    CN119133601A